Avaliação da resistência à corrosão do aço alto manganês: efeito da laminação a frio e temperatura do eletrólito - Figueiredo, Yara Amorim de (2024)
Progress in developing advanced steels has been outstanding, driven by the growing need for lightweight materials with good mechanical performance and corrosion resistance. High manganese (Mn) steels, with a composition of 12 - 30%, are iron alloys with the TWIP (Twinning Induced Plasticity) effect, giving these materials a unique combination of mechanical strength and ductility. However, there are few studies in the literature on the corrosion resistance of this material. Therefore, this study aimed to analyze the influence of cold rolling on the corrosion resistance of the Fe-Mn alloy. In addition, the influence of increasing the electrolyte temperature on corrosion kinetics was studied. In this work, the electrochemical and microstructural behavior of an experimental Fe-Mn alloy (26 % wt. Mn) in an electrolytic NaCl solution (0.01M) was evaluated, taking into account different thickness reductions (0, 30, 50, and 70 %) and electrolyte temperature ranges (25, 35 and 45°C). electrochemical techniques such as open circuit potential (OCP) monitoring, potentiodynamic linear polarization (PP), and electrochemical impedance spectroscopy (EIS) were used. In addition, mass loss tests and analysis by optical microscope (OM), scanning electron microscopy (SEM) and elastic scattering spectroscopy (ESS), were carried out to evaluate the surface of the material. For mechanical characterization, the Vickers microhardness test was carried out. The results showed that the cold rolling process gradually increased the number of maclas due to the stress applied during the procedure. The Vickers microhardness value was doubled with the 30% thickness reduction, compared to the sample as received, and its increase was more pronounced for the material rolled at 50% and 70%. The primary corrosion mechanism observed was generalized corrosion. The effect of temperature in the electrolyte was investigated as it influenced the kinetics of the reactions, in which an increase in current density was observed in the PP tests. The EIS tests indicated that the increase in temperature resulted in decreased polarization resistance. No significant change in corrosion resistance was observed about the effect of cold rolling, showing similar values in all the electrochemical tests and consistent with the mass loss tests.